Peripartum cardiomyopathy in uncorrected tetralogy of fallot: a case report - Phutane, Mukund Vasantrao; Kal, Varsha Ansaram; Patil, Vishal Vijayrao; Bansal, N. O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Tetralogy of Fallot (ToF) is the most common cyanotic congenital heart with incidence about 10% of all congenital heart disease. Natural survival to the fourth decade is extremely rare (only about 3%), but there is a tendency of increasing number of women with cyanotic congenital heart disease living 3 to 4 decades and are becoming pregnant. Because of significant physiology adaptation and changes, pregnancy and delivery process are troublesome for most unhealthy women, including those with uncorrected ToF. For ToF patients, it remains an important cause of maternal morbidity (62.5%), and even mortality (10%) and has significant effects on fetal outcome. Discussed below a case of pregnancy in a 30 year old woman with uncorrected ToF, dyspnoea class II of New York Heart Association, on 36th week pregnancy with complication of postpartum cardiomyopathy. Through dedicated medical care, patient’s condition improvement can be seen. Prognosis of pregnancy in patient with uncorrected ToF is poor without optimal obstetrical and medical management.